Financial development and economic growth: An empirical analysis for Ireland - Antonios Adamopoulos (International Journal of Economic Sciences and Applied Research, 2010)
This study investigated the relationship between financial development and economic growth for Ireland for the period 1965-2007 using a vector error correction model (VECM). Questions were raised whether financial development causes economic growth or reversely taking into account the positive effect of industrial production index. Financial market development is estimated by the effect of credit market development and stock market development on economic growth. The objective of this study was to examine the long-run relationship between these variables applying the Johansen cointegration analysis taking into account the maximum eigenvalues and trace statistics tests. Granger causality tests indicated that economic growth causes credit market development, while there is a bilateral causal relationship between stock market development and economic growth. Therefore, it can be inferred that economic growth has a positive effect on stock market development and credit market development taking into account the positive effect of industrial production growth on economic growth for Ireland.
Keywords: O11; C22; 330; financial development; economic growth; Granger causality